Impact of Adding Poly-herbal Preparations and Mustard Oil Supplements on the Reproductive and Production Performance of Sahiwal Cows - , Subhash Chandra; , Chandan Kumar; , P S Oberoi (Archives of Current Research International, 2025)
The present experiment was conducted to evaluate the effect of supplementation with mustard oil and poly-herbal preparations on the productive and reproductive performance of Sahiwal cows. For this study, 40 Sahiwal cows were selected 30 days before calving, and these Sahiwal cows were randomly divided into four groups (control T0 group and supplemented T1, T2 and T3 groups), with 10 animals in each group. Group T1 was supplemented with mustard oil, group T2 was supplemented with a poly-herbal preparations, and group T3 was supplemented with both mustard oil and the poly-herbal preparations. However, group T1 (n = 10) received an additional 200 ml of mustard oil from 21 days before calving to 21 days after calving, group T2 (n = 10) received an additional poly-herbal preparation (150 g herbal mixture, 25 g kalanamak, and 250 g jaggery) and fed it to the cow up to seven days from the date of calving, and group T3 (n = 10) received an additional mustard oil as T1 group and an additional poly-herbal mixture as T2 group. The poly-herbal mixture was prepared by mixing six herbs (Methi, Ajwain, Sanuf, Sowa, Sundh and Bari Elaichi), as well as jaggery and kalanamak (black salt). Animals in the supplemented and control groups received rations as per the NRC's (2001) feeding schedule. The results depicted lower incidences of RFM (retention of fetal membrane) in the supplemented groups, i.e., T1 (20%), T2 (10%), and T3 (10%), as compared to the control group (30%). The time required for expulsion of the placenta was significantly (P<0.05) lower in the supplemented (T1, T2, and T3) groups as compared to the control (T0) group. The average days to first insemination/AI were significantly (P <0.05) lower in the supplemented groups as compared to the control group. The service period in Sahiwal cows supplemented with a poly-herbal mixture and mustard oil (T1, T2, and T3) was significantly lower (P <0.05) than in the control group. There was an improvement in conception rate in T1 (19%), T2 (12%), and T3 (24%), compared to the T0 group. The incidence of metritis was lower in the supplemented groups T1(20%), T2(10%) and T3(10%) as compared to the control group (T0-30%). Milk yield recorded up to 12 weeks was significantly (P<0.05) higher in T2 and T3 groups as compared to the control group (T0). The mean values of BHBA and NEFA concentrations were significantly (P<0.05) lower in T1 and T3 as compared to the T0 respectively. Supplementation of mustard oil and a poly-herbal mixture safely included in the diet of peri-parturient animals subsequently helps in improving the reproductive efficiency and productive performances of Sahiwal cows.